A displacement formulation for cylindrical shells under radial loads - Madureira, Luísa (2013)
A displacement formulation for cylindrical shells subjected to radial loads is presented. Static loads are applied to straight thin pipes using a variational method and results are compared both to finite element analysis and a shell element from Ansys program. The formulation includes a combination of trigonometric functions in two variables, longitudinal and circumferential direction. Then a system of differential equations is solved for two different load cases and the vertical displacement is obtained in the points where the load is applied.